Exploring food insecurity, food waste, and dietary diversity among rural and urban households of Lesotho - Molapo, Maletsie (University of the Free State, 2023)
Lesotho is one of the sub-Saharan African countries that perpetually struggles with food insecurity. Consumers in Lesotho still waste food despite living in a low-income country. Most people live under the poverty line of US$1.00 per day and low-income households consume meals that are low in diversity, which elevates micronutrient deficiencies. Consequently, many children under five years of age experience stunting, obesity, and micronutrient deficiencies due to a lack of food or insufficient intake. The study sought to explore household food insecurity, estimate the quantity of household food waste, determine household dietary diversity, and identify food preservation techniques in rural and urban areas of Lesotho. The research was conducted in four of the 10 districts of Lesotho, namely Mafeteng, Thaba-Tseka, Leribe, and Qacha’s Nek. The sample size was 440 households, and stratified random sampling was used for the selection of participating households. A mixed-methods approach was utilised and an exploratory descriptive design was adopted. Both structured questionnaires and interviews were employed, which represented quantitative and qualitative elements. The questionnaire addressed socio-demographics, the Household Food Insecurity Access Scale (HFIAS), food waste, the Household Dietary Diversity Score (HDDS), and food preservation. The consumers who participated in the study were 18 years and older. The analysis was conducted using the Statistical Package for the Social Sciences, and Fisher’s exact test was used to compare variables. Food insecurity was significantly higher in the rural areas than the urban areas, where four categories were measured, namely food secure, mildly food insecure, moderately food insecure, and severely food insecure. Indicators of food insecurity were to be being a female, being unemployed, and cooking with open fire. Using liquefied petroleum gas (LPG) and electricity for cooking significantly were found to reduce food insecurity. Total food waste estimations were calculated at 190.9 kg (rural) and 156.2 kg (urban) per week, resulting in annual estimated food waste of 13 003.2 kg (rural) and 7 496.8 kg (urban), totalling 20, 500 kg of household food waste in Lesotho annually. The main ways that consumers discard food waste in both rural and urban areas are using compost heaps, discarding it in the garbage bin, and burying it. All these were significant predictors of food waste even though they had a weak correlation. It is also a common practice to give food waste to animals. The main reasons for food waste in both the rural and urban areas were that consumers like to eat fresh food, they are too busy to cook planned meals, food is left too long in the refrigerator/freezer, they buy too much food, they do not check the cupboard or refrigerator/freezer before going shopping, and some members of the household do not always finish eating their food. Food groups that are not wasted in large quantities in rural and urban are fruits, vegetables, milk and dairy products, legumes, and grains. The dietary diversity of the rural and urban areas differs significantly, with diversity in the urban areas being higher than in the rural areas. Food groups mostly consumed are cereals (soft/stiff porridge and bread) and leafy green vegetables (rape, cabbage, and spinach). Fruits are mostly consumed when they are in season because they are expensive otherwise. Factors that significantly contribute to increasing the HDDS are using electricity and LPG for cooking. Factors that significantly decrease the HDDS are being female, cooking with an open fire, and purchasing food every two weeks. More consumers preserve food in urban areas than in rural areas, and the prominent techniques for preserving food are sun drying and bottling, while fewer consumers in both rural and urban areas consider salting and freezing. Food insecurity is still high, even though diversity is promising. It is therefore recommended that the creation of awareness be established, through policies and other platforms regarding, household food waste, food security and eating patterns.
Dissertation (M.Sc.(Consumer Science))--University of the Free State, 2023
Keywords: Food insecurity; Food waste; Dietary diversity; Food preservation; Lesotho; Food security